Integrity as a Contingency in Asset Misappropriation: Behavioral and Fraud Risk Perspectives - Tertiarto Wahyudi; Umi Kalsum; Mukhtaruddin Mukhtaruddin; Rika Henda Safitri; Syarahfina Aprilisia (Integrated Journal of Business and Economics (IJBE), 2026)
Abstract The study aims to analyze the influence of manager behavior, fraud risk elements, and integrity on asset misappropriation at a banking branch office in Palembang. The population of this research is managers of banking branch offices in Palembang who have been registered with the Financial Services Authority.The sample was determined based on a simple random sampling technique, namely 80 respondents. Data collection techniques used in this research are literature study and questionnaires. The results showed that moral obligation, pressure, and rationalization had a positive and significant effect on asset misappropriation. Meanwhile, behavior towards fraud, subjective norms, perceived behavioral control, opportunities, and abilities have no significant effect on asset misappropriation. In addition, integrity is able to moderate the influence attitude toward the fraud, perceived behavioral control, opportunity, rationalization and capability with asset misappropriation.